VD_FINDINFO Réc-civile / 2021 / 13 vom 8. März 2021 - VD Tribunal cantonal (2021)
RÉCUSATION, DROIT À UNE AUTORITÉ INDÉPENDANTE ET IMPARTIALE | 47 al. 1 let. a CPC (CH), 47 al. 1 let. f CPC (CH), 49 al. 1 CPC (CH), 8a al. 1 CDPJ, 8a al. 3 CDPJ